Examining Public Accountability in the Digital Era: Evaluating the Effectiveness of SP4N-LAPOR! at Diskominfo Aceh Tamiang - Anwar Anwar; Masdalifah Sembiring; Zulkarnain Zulkarnain; Samsuar Samsuar (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2026)
Public accountability has become a key concern in the digital era as governments increasingly rely on digital platforms to improve transparency, responsiveness, and citizen participation in public service delivery. In Indonesia, SP4N-LAPOR! functions as the national online public complaint system that connects citizens with government institutions. This study evaluates the effectiveness of SP4N-LAPOR! in promoting public accountability at the Aceh Tamiang Department of Communication, Informatics, and Encryption (Diskominfo). Guided by Mark Bovens’ Public Accountability Theory, the study examines the platform’s role as an accountability mechanism and identifies the institutional challenges affecting complaint management. A descriptive qualitative approach was employed using observations, semi-structured interviews, and document analysis. The data were analyzed thematically to relate the empirical findings to public accountability theory and the broader digital governance literature. The findings indicate that SP4N-LAPOR! has improved institutional accountability by providing citizens with an accessible channel to submit complaints, aspirations, and requests for public information. However, its effectiveness remains limited by delayed responses from liaison agencies, weak inter-agency coordination, insufficient public outreach, low digital literacy among some citizens, and occasional network disruptions. These findings demonstrate that the effectiveness of digital complaint platforms depends not only on technological infrastructure but also on institutional responsiveness, coordination, and organizational commitment. This study contributes to the digital governance literature by extending the evaluation of e-government initiatives beyond technical performance and emphasizing public accountability as a critical indicator of effective digital public service delivery.